High school female basketball athletes exhibit decreased knee-specific choice visual-motor reaction time - Nagai, T.; Schilaty, N. D.; Bates, N. A.; Bies, N. J.; McPherson, A. L.; Hewett, T. E. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Weaker hamstrings muscular forces and lower ratio of the hamstrings/quadriceps muscular forces in female athletes have been identified as modifiable risk factors for anterior cruciate ligament (ACL) injuries. However, sex differences in athletes` ability to react to visual cues (Choice Visual-Motor Reaction Time: VMRT) and to generate knee muscular forces (rate of force development: RFD) immediately following the visual cues were largely unknown. Therefore, the purpose of the study was to examine sex differences in Choice VMRT and RFD. A total of 50 high school basketball athletes (26F/24 M) participated in the study. Subjects sat in the knee dynamometer chair with their knee secured at 70° of knee flexion and performed knee extension or flexion maximum voluntary isometric contractions immediately after they saw the visual cue: "UP" or "DOWN" arrows, respectively. Choice VMRT was defined as the time between the visual cue and the initiation of muscular force development (>5Newtons). RFD was calculated by dividing the changes in forces over the changes in time at four time points (0-50/100/150/200 ms). Peak muscular forces and RFD were normalized to their body mass. Average of three trials in each direction (flexion and extension) in each leg was used for statistical analyses. Females had significantly slower Choice VMRT (p < 0.001-0.027) and lower knee extension RFD at 100 ms (p = 0.005). In addition, females had significantly higher knee flexion/extension ratio than males in late RFD (150 ms and 200 ms) (p < 0.004). The current study has provided additional sensorimotor characteristics of athletes and sexes in addition to their knee muscular characteristics.